THE ACADEMICAL INTEGRITY CONCEPT: SCIENTIFIC DISCOURSE - Sopova, Dana (Continuing Professional Education: Theory and Practice, 2019)
In the article is represented the role of the academical integrity as a part of the university education phenomenon, professional training of the future specialists; the essence of the academical integrity concept and its semantic content of the competent students and scholars formation; defined attitude toward plagiarism among undergraduates and young researchers. The author examines the increasing number of the violations of the principles of academical integrity in the Ukrainian academic community educational activities. The European practice of the development of academical integrity in the formation of professional and ethical competence of future teachers is seen as a model for Ukraine to overcome such problems of academical dishonesty as cheating, plagiarism, dishonest receiving of marks. Academical integrity is a complex term that describes a kind of agreement between all members of the academical community - teachers, students and the administration of the educational establishment. It is based on ethical values which the student comes to university, enriching them during education and does not end when the graduate receives a diploma. The ability to be responsible, honest, treated tolerant to the points of view of other people, think critically, to observe ethics in your actions – there a components that are forming concept of academical integrity, and including in the list of the competent students and researchers characteristics. Academical integrity – it is a set of rules and ethical principles that are defined by the legislation and all participants in the educational process in teaching, learning and proceeding creativity should be using to ensure confidence in the results of studies and creative achievements. Ethical rules and principles inherent in the Ukrainian people mentality, so understanding the rules of behavior that are based on the positive internal motivation is a natural phenomenon for PhD students, young researchers and students that it is only necessary to explain and provide appropriate support. We must understand that academical integrity is a moral and ethical category, which is the foundation established norms and rules of behavior for scientists who provide freedom while doing teaching and researching tasks.